Reduction of sitting time has a positive effect on the decrease of insulin resistance in patients with non-alcoholic fatty liver disease - Sabinicz, Anna; Maciejewska, Dominika; Kaczorowska, Małgorzata; Ryterska, Karina; Jamioł-Milc, Dominika; Wyszomirska-Raszeja, Joanna; Gutowska, Izabela; Stachowska, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Non-alcoholic fatty liver disease (NAFLD) affects a large part of the human population. One of the major environmental factors associated with the risk of NAFLD is the lack of physical activity. Aim: To compare the level of physical activity and the insulin resistance in NAFLD patients. Material and methods: Thirty patients with NAFLD underwent a six-month dietary intervention based on the principles of classical dietetics. Data about diet and physical activity was based on 72-hour nutrition diaries and International Physical Activity Questionnaire (IPAQ). Standard blood biochemical analyses were carried out before and after diet at the University Hospital Laboratory. Results: The study showed that total physical activity and physical activity in leisure time are negatively correlated with insulin resistance (HOMA-IR) (p < 0.05). Insulin (p < 0.05), body weight (p < 0.05), and waist-hip ratio (WHR) (p < 0.05) were also negatively correlated with physical activity in free time. In addition, we noticed a positive correlation between sitting time and the risk of insulin resistance, in the case of HOMA-IR and insulin concentration (p < 0.05). Conclusions : Dietary intervention and a physical activity plan are important factors in the treatment of non-alcoholic fatty liver disease. Taking regular exercise increases insulin sensitivity and prevents further development of the disease. It seems that diet and physical activity are not the only one risk factors of NAFLD. Our study reveals that the reduction of sitting time has a positive effect on the level of insulin and it reduces insulin resistance in patients with NAFLD.